1993
DOI: 10.1152/ajpcell.1993.264.4.c912
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the arachidonic acid cascade dissociate 48/80-induced Ca2+ influx and Ca2+ release in mast cells

Abstract: Effects of inhibitors of the arachidonic acid cascade on Ca2+ release from intracellular stores and Ca2+ influx through the plasma membrane during stimulus-secretion coupling were examined using rat peritoneal mast cells loaded with fura-2. Compound 48/80 (48/80) was used as a secretagogue. A phospholipase inhibitor, p-bromophenacyl bromide (PBPB), or a lipoxygenase inhibitor, nordihydroguaiaretic acid (NDGA), inhibited the 48/80 (1 microgram/ml)-induced release of histamine, Ca2+, and Mn2+ influxes, but the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 7 publications
3
6
0
Order By: Relevance
“…Consistent with previous work (Kuno et al, 1993), NDGA blocked mast cell degranulation. Other studies have shown that piroxicam, meloxicam, NS-398 (COX-2 inhibitor) and acetylsalicylic acid (aspirin, a COX-1/COX-2 inhibitor) treatment can prevent rat mast cells from releasing histamine following antigen-dependent (IgE) mediated stimulation (Grosman, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous work (Kuno et al, 1993), NDGA blocked mast cell degranulation. Other studies have shown that piroxicam, meloxicam, NS-398 (COX-2 inhibitor) and acetylsalicylic acid (aspirin, a COX-1/COX-2 inhibitor) treatment can prevent rat mast cells from releasing histamine following antigen-dependent (IgE) mediated stimulation (Grosman, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…In isolated rat hepatocytes (Karara, Breyer, Falck & Capdevila, 1991), pituitary cells (Snyder, Lattanzio, Yadagiri, Falck & Capdevila, 1986), parotid cells (Snowdowne, Rosenoer, Yu & Cashman, 1989) and epithelial cells (Madhun, Goldthwait, McKay, Hopfer & Douglas, 1991), 5,6-EET increases [Ca2+], due to the direct stimulation of Ca2+ entry. Additional data provided evidence for a cyclo-oxygenase-related Ca2+ release with higher concentrations of 5,6-EET (Kuno, Kawawaki, Shibata & Gotani, 1993). Our findings that 5,6-EET failed to increase [Ca2+]i in Ca2+-free solution and that cyclooxygenase inhibition did not affect 5,6-EET-induced Ca2+ entry strongly suggest a direct stimulation of endothelial Ca2+ entry by this P450 MO product (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…In endothelial cells, Goligorsky, Menton, Laszlo & Lum (1989) provided strong evidence for the involvement of phospholipase A2 activation in thrombin-induced sustained Ca2+ entry. A key role of phospholipase A2 stimulation for agonist-stimulated Ca2+ entry was also described in mast cells (Kuno et at. 1993).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The fura-2 acetoxymethyl ester was dissolved in dimethyl sulfoxide to a concentration of 1 mM. Purified peritoneal mast cells (10 6 cells/ml) or HEK293 (10 6 cells/ml) were incubated with a final concentration of 1 M fura-2 in bovine serum albumin (0.1%)-HEPES buffer for 30 min at 37°C as described previously (Kuno et al, 1993). The cells were washed twice in HEPES buffer by centrifugation (150g, 4°C, 5 min), to remove the fura-2 that had not been taken up into the cell.…”
Section: Methodsmentioning
confidence: 99%